Book Review: Maxim Storchevoy, A Scientific Approach to Ethics: Developing Greater Respect for Ethics in Business and Society. (January 2019) - Borthakur, Anwesha
Maxim Storchevoy, A Scientific Approach to Ethics: Developing Greater Respect for Ethics in Business and Society, United Kingdom: Palgrave Macmillan, 2018. 147 pages. ₹147. ISBN: 978-3-319-69112-1.